Determinants of E-learning Acceptance among Agricultural Extension Agents in Malaysia: A Conceptual Framework - Mangir, Safaie; Othman, Zakirah; Udin, Zulkifli Mohamed (International Review of Management and Marketing, 2017)
The objective of this paper is to develop a framework on e-learning acceptance among agricultural extension agents in Malaysian agricultural sector. E-learning is viewed as a solution in response to the increasing need for learning and training. This paper will review past literatures for the relevant factors that influence behavioral intention for e-learning acceptance as well as the relevant behavioral theories that provide the foundation for developing research framework to illustrate the relationship between the factors and behavioral intention for e-learning acceptance. The outcome of this research is the proposed framework that demonstrates the relationship between the factors and behavioral intention for e-learning acceptance. Understanding the determinants of e-learning acceptance will lead to the development of more effective and meaningful e-learning services. The research outcome will help to increase the interest to use e-learning, improve the policies and infrastructure, widen the availability and increase user engagement. Investigating the ability of the behavioral theory in predicting e-learning acceptance in agricultural setting will be useful for comparison in the future studies in different settings. Keywords: Acceptance, Agriculture, E-learning, Extension Agent JEL Classifications: Q13, D83